Native hip hop: coyote recreates story and song - Dunstan, Runningwater Dawn (Author); Mills, Antonia (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2005)
I intend to examine Native hip hop and its capacity to address social and political issues, empower and give voice to youth, and revitalize elements of oral tradition within a modern context. Qualitative inquiry grounded in the phenomenological tradition constitutes the research design for this study. lll Methodology includes primary research comprised of both interviews with Native hip hop artists as well as my own personal experience with hip hop; and secondary research including academic literature, internet, and other non-academic sources such as magazines, newspapers and audio disks. Native hip hop is a recent phenomenon in Canada, and scholarly literature on the subject is sparse. This study expands the scholarship in the discipline and recognizes the important segment of Native youth, their messages and contributions as hip hop artists to the hip hop community as well as contemporary Canadian First Nations culture. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1296272